Circulating tumor necrosis factor‐α, interleukin‐1β, and interleukin‐17A estimates increased major adverse cardiac event risk in acute myocardial infarction patients. Issue 5 (6th March 2023) - Guo, Jing; Hu, Zhenfeng; Ren, Liang; Zhao, Weibo; Zuo, Ruijing; Guo, Shuang; Jia, Chaoguo; Gao, Wei
Abstract: Background: Inflammatory cytokines are implicated in the development of atherosclerosis and cardiomyocyte injury during acute myocardial infarction (AMI). This study aimed to investigate the correlation of eight common inflammatory cytokines with major adverse cardiac event (MACE) risk and further establish a prognostic model in AMI patients. Methods: Serum samples of 210 AMI patients and 20 angina pectoris patients were, respectively, collected at admission, to detect tumor necrosis factor‐alpha (TNF‐α), interleukin (IL)‐1β, IL‐6, IL‐8, IL‐10, IL‐17A, vascular cell adhesion molecule‐1 (VCAM‐1), and intercellular adhesion molecule 1 (ICAM‐1) via enzyme‐linked immunosorbent assay. Results: TNF‐α, IL‐6, IL‐8, IL‐17A, VCAM‐1, and ICAM‐1 were elevated (all p < 0.050); IL‐10 ( p = 0.009) was declined; IL‐1β ( p = 0.086) was not varied in AMI patients compared with angina pectoris patients. TNF‐α ( p = 0.008), IL‐17A ( p = 0.003), and VCAM‐1 ( p = 0.014) were elevated in patients with MACE occurrence compared to patients without MACE occurrence; meanwhile, they possessed a relatively good value for identifying MACE risk via receiver‐operating characteristic (ROC) analysis. Subsequent multivariate logistic regression analysis revealed that the independent risk factors for MACE contained TNF‐α (odds ratio (OR) = 1.038, p < 0.001), IL‐1β (OR = 1.705, p = 0.044), IL‐17A (OR = 1.021, p = 0.009), history of diabetes mellitus (OR = 4.188, p = 0.013), history of coronary heart disease (OR = 3.287, p = 0.042), and symptom‐to‐balloon time (OR = 1.064, p = 0.030), whose combination disclosed a satisfying prognostic value for MACE risk (area under the curve: 0.877, 95% CI: 0.817–0.936). Conclusion: Elevated levels of serum TNF‐α, IL‐1β, and IL‐17A independently correlated with MACE risk in AMI patients, which perhaps provide novel auxiliary for AMI prognostic prediction. Abstract : Serum samples of 210 acute myocardial infarction (AMI) patients and 20 angina pectoris patients were collected at enrollment for the determination of eight inflammatory cytokines. Interestingly, tumor necrosis factor‐alpha (TNF‐α), interleukin (IL)‐6, IL‐8, IL‐17A, vascular cell adhesion molecule‐1 (VCAM‐1), and intercellular adhesion molecule 1 (ICAM‐1) were elevated (all p < 0.050); IL‐10 ( p = 0.009) was declined; IL‐1β ( p = 0.086) was not varied in AMI patients compared with angina pectoris patients. TNF‐α ( p = 0.008), IL‐17A ( p = 0.003), and VCAM‐1 ( p = 0.014) were elevated in patients with (vs. without) major adverse cardiac event (MACE) occurrence. Moreover, the independent risk factors for MACE contained TNF‐α, IL‐1β, IL‐17A, history of diabetes mellitus, history of coronary heart disease, and symptom‐to‐balloon time (all p < 0.050), whose combination disclosed a satisfying prognostic value for MACE risk (area under the curve: 0.877, 95% CI: 0.817–0.936). In summary, elevated serum TNF‐α, IL‐1β, and IL‐17A independently correlated with MACE risk, which perhaps provide novel auxiliary for AMI prognostic prediction.